2019
DOI: 10.1159/000496100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Network Analysis of the Urinary Proteome of Alzheimer’s Disease Patients

Abstract: Background/Aims: The identification of predictive biomarkers for Alzheimer’s disease (AD) from urine would aid in screening for the disease, but information about biological and pathophysiological changes in the urine of AD patients is limited. This study aimed to explore the comprehensive profile and molecular network relations of urinary proteins in AD patients. Methods: Urine samples collected from 18 AD patients and 18 age- and sex-matched cognitively normal controls were analyzed by mass spectrometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 73 publications
(76 reference statements)
0
33
0
Order By: Relevance
“…GOT1 is localized in the cytoplasm and acts as a scavenger of glutamate in brain neuroprotection. To our knowledge, there is only scarce data on its specific functions in neurons or synapses, but GOT1 activity was found to be increased in CSF (D’Aniello et al ) and urine (Watanabe et al ) of patients with Alzheimer disease compared to controls. The SNO site described in this study on position 46 of the human sequence has been previously found in a technical setting (Forrester et al ).…”
Section: Discussionmentioning
confidence: 99%
“…GOT1 is localized in the cytoplasm and acts as a scavenger of glutamate in brain neuroprotection. To our knowledge, there is only scarce data on its specific functions in neurons or synapses, but GOT1 activity was found to be increased in CSF (D’Aniello et al ) and urine (Watanabe et al ) of patients with Alzheimer disease compared to controls. The SNO site described in this study on position 46 of the human sequence has been previously found in a technical setting (Forrester et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, to designate a specific substance as a biomarker, a high-throughput method or an educated guess is necessary. Therefore, despite its cost, MS-based proteomic analysis and metabolic profiling of urine from patients with a specific disease is gaining prominence to identify a novel disease-specific biomarker [14][15][16]. If the target material is nucleic acid, next generation sequencing or small RNA sequencing can be a tool for a high-throughput screening method [17].…”
Section: Detection Methodsmentioning
confidence: 99%
“…Lipoprotein metabolism, heat shock protein 90 signaling pathway, and matrix metalloproteinase signaling pathway as well as redox regulation by thioredoxin were among the molecular pathways with the highest enrichment scores, providing evidence for impairment of vascular processes key to the development of dementia (66). In addition, Watanabe et al (66) also supplemented their functional GO and KEGG analyses with an interrelation network analysis to determine, which of the proteins differentially expressed in the Alzheimer' s urine samples interact with each other (either directly or via an intermediate). This network analysis of molecular relationships enabled these researchers to further elucidate which GO biological processes and KEGG pathways should be prioritized in future studies and whether they correlate with and confirm other findings.…”
Section: The Impact Of Improving the Go Resource On Data Interpretationmentioning
confidence: 99%
“…GO term enrichment analysis has also been implemented in pilot studies aiming to identify biomarkers associated with dementia, which can be detected using noninvasive methods in easily accessible bodily fluids, such as blood (65) and urine (66). For instance, Chouliaras et al (65) used GO enrichment together with KEGG pathway analysis to demonstrate the relationships between the identified blood biomarkers with neurological processes and neuronal components.…”
Section: The Impact Of Improving the Go Resource On Data Interpretationmentioning
confidence: 99%
See 1 more Smart Citation